Five Years of Clinical Evaluation of Nonresorbable Membranes in the Treatment of Intrabony Defects Following Guided Tissue Regeneration - Nagira, Tamaki; Mori, Atsushi; Ishikawa, Kazuhiro; Tohya, Tosyo; Suzuki, Hiroki; Amano, Katsuhiko; Noguchi, Toshihide; Nishiyama, Saeko; Inagaki, Koji; Koide, Masanori; Yoshinari, Nobuo (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1996)
The aim of the present study was to evaluate whether new attachment, gained following guided tissue regeneration (GTR) therapy, can be maintained over 5 years of maintenance therapy. Fourteen sites in 14 patients (average age 40.9 years, 21-57 years of age, 3 males and 11 females) with adult periodontitis were treated with the GTR technique (GTR group) and 14 sites in 14 patients average age 39.6 years, 23-54 years of (age, 5 males and 9 females) with adult periodontitis were treated with flap debridement (FOP group). Lesions in the GTR group included 1 site with a single wall defect, 11 sites with 2 intrabony wall defects and 2 sites with 3 intrabony wall defects. Lesions in the FOP group included 2 sites with a single wall defect, 9 sites with 2 intrabony wall defects and 3 sites with 3 intrabony wall defects. The sites which had undergone both procedures demonstrated improved gingival conditions including probing pocket depth (PD), clinical attachment level (CAL) and marginal tissue recession (MR) at 5 years after surgery. In the GTR and FOP groups, there were decreases in PD of 3.9±1.6mm and 2.9±1.5mm, gains in CAL of 3.2±1.8mm and 1.1±1.4mm and increases in MR of 0.7±1.3mm and 1.8±1.5mm, respectively. A significant attachment gain was obtained in the GTR group and this gain was significantly longer than that in the FOP group. During the 4 years of maintenance between the 1 and 5 year examinations, PD and CAL in both groups remained stable. These results demonstrate that CAL, obtained as the result of GTR therapy, can be maintained for periods of up to 5 years.